Relationship between Abdominal Pressure, Pulmonary Compliance, and Cardiac Preload in a Porcine Model - Joost Wauters; Piet Claus; Nathalie Brosens; Myles McLaughlin; Greet Hermans; Manu Malbrain; Alexander Wilmer (Critical Care Research and Practice)
Rationale. Elevated intra-abdominal pressure (IAP) may compromise respiratory and cardiovascular function by abdomino-thoracic pressure transmission. We aimed (1) to study the effects of elevated IAP on pleural pressure, (2) to understand the implications for lung and chest wall compliances and (3) to determine whether volumetric filling parameters may be more accurate than classical pressure-based filling pressures for preload assessment in the setting of elevated IAP. Methods. In eleven pigs, IAP was increased stepwise from 6 to 30 mmHg. Hemodynamic, esophageal, and pulmonary pressures were recorded. Results. 17% (end-expiratory) to 62% (end-inspiratory) of elevated IAP was transmitted to the thoracic compartment. Respiratory system compliance decreased significantly with elevated IAP and chest wall compliance decreased. Central venous and pulmonary wedge pressure increased with increasing IAP and correlated inversely (r=-0.31) with stroke index (SI). Global end-diastolic volume index was unaffected by IAP and correlated best with SI (r=0.52). Conclusions. Increased IAP is transferred to the thoracic compartment and results in a decreased respiratory system compliance due to decreased chest wall compliance. Volumetric filling parameters and transmural filling pressures are clearly superior to classical cardiac filling pressures in the assessment of cardiac preload during elevated IAP.